MENGELOLA RESIKO KETIDAKPATUHAN UPAH MINIMUM: STUDI KASUS PADA PT BIOMASSAL NUSANTARA DESA TERANG BULAN - Sri Pujiyama Pasaribu; Arsyadona; Aisya Trixsi Pramaisela; M Ramadhan AI Ansari; Yeni Inayah (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
Managing non-compliance with minimum wage regulations is a serious issue in the Indonesian industrial sector, especially in companies operating in remote areas. This article analyzes the case of PT Biomassal Nusantara in Terang Bulan Village, North Sumatra which has not complied with regional minimum wage standards. These issues present legal, reputational and productivity risks that can threaten a company's sustainability. The aim of this research is to identify and assess the risks posed by noncompliance with minimum wages at PT Biomassal Nusantara and provide mitigation recommendations based on the Enterprise Risk Management (ERM) approach. The research results show that noncompliance increases the risk of fines, lawsuits and reputational harm, and has a negative impact on employee motivation and productivity. This article recommends standardized wage policies, compliance education for management and staff, and regular audits to ensure the accuracy of compensation management. Compliance with minimum wage regulations has proven to be not only legally important, but also strategic for building sustainability and good relations with the community and employees.